2016
DOI: 10.2151/sola.2016-002
|View full text |Cite
|
Sign up to set email alerts
|

Development Processes of Oceanic Convective Systems Inducing the Heavy Rainfall over the Western Coast of Sumatra on 28 October 2007

Abstract: This study analyzed the oceanic convective systems that induced heavy rainfall over the western coast of Sumatra on 28 October 2007. The convective systems that satisfied the definition of a mesoscale convective complex (MCC), as identified by infrared satellite imagery, developed repeatedly for 16 hours over the Indian Ocean near Sumatra. The MCC developed from midnight on 27 October until the early morning of 28 October, and it was intensified by the land breeze from Sumatra. New convective systems around th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Alternatively, the role of a cold pool (e.g. Teo et al, 2011;Trismidianto et al, 2016) may serve as a concrete and testable hypothesis to be the manifestation of the so-called selfreplicating mechanism proposed by Mori et al (2004). We additionally found that the CENS associated with EMP may have a more localized origin and seems to involve mesoscale air-sea interactions over the South China Sea, which is also of interest to address in our future study.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Alternatively, the role of a cold pool (e.g. Teo et al, 2011;Trismidianto et al, 2016) may serve as a concrete and testable hypothesis to be the manifestation of the so-called selfreplicating mechanism proposed by Mori et al (2004). We additionally found that the CENS associated with EMP may have a more localized origin and seems to involve mesoscale air-sea interactions over the South China Sea, which is also of interest to address in our future study.…”
Section: Discussionmentioning
confidence: 66%
“…In an earlier study, Mori et al (2004) reported that precipitating systems may propagate seaward or landward from coastal regions in Sumatra. A more recent study by Trismidianto et al (2016) indicates that convection over coastal regions in Sumatra can also be induced by a decaying oceanic convective system. From results of a numerical study, Li et al (2017) show that offshore or onshore rainfall propagation may occur over the coastal region of the MC all year round.…”
Section: Introductionmentioning
confidence: 99%
“…Similar or extension to this study will take more benefit from better satellite rainfall products. We have not yet investigated the mechanisms responsible for the propagation of the coastal 10 precipitation but the role of cold pool (e.g., Teo et al, 2011;Trismidianto et al, 2016) may serve as a concrete and testable hypothesis to be the manifestation of the so-called self-replicating mechanism proposed by Mori et al (2004). We additionally found that the CENS associated with EMP may have more localised origin and seems to involve mesoscale air-sea interactions over the South China Sea, which is of interest to address in our future study.…”
Section: Discussionmentioning
confidence: 99%
“…In an earlier study, Mori et al (2004) reported that precipitating systems may propagate seaward or landward from coastal region in Sumatra 15 Island. A more recent study by Trismidianto et al (2016) indicates that convection over coastal region in Sumatra Island can also be induced by a decaying oceanic convective system. From results of a numerical study, Li et al (2017) show that offshore or onshore rainfall propagation may occur over coastal region of the MC all around year.…”
mentioning
confidence: 99%
“…LAPAN is the Indonesian space agency, founded in 1963. Along with space programs, it conducts atmospheric research (e.g., Trismidianto et al 2016; Noersomadi and Tsuda 2017) by maintaining 10 ground-based stations and research facilities throughout Indonesia. They include meteor wind radar (Tsuda et al 1995), wind profilers (Schafer et al 2003), an X-band radar (Oigawa et al 2017), and the Equatorial Atmosphere Radar.…”
mentioning
confidence: 99%